Detection Mechanism against the Attacks in MANET and Biometric Classification - Prabhusundhar, P; Srinivasan, B; Ramalingam, M (International Journal of Computer Sciences and Engineering, 2025)
Blackhole attack revealing, PCBHA (Prevention of a Co-operative Black Hole Attack) is a reviewed AODV routing protocol that is proposed in order to avert cooperative black holes. First, it runs each authorized user with a default fidelity level and after spreading a RREQ, a source node waits to accept resumed RREPs from the adjoining nodes and then chooses a near node of a greater fidelity level, which exceeds the threshold value, for passing the information packs. The target node will yield an ACK note after getting information packets, and the source node may add 1 to the fidelity level of the adjacent node, upon receiving of an ACK answer. If no ACK reaction is established, 1 is deducted from the fidelity level, which shows a potential black hole node on this route and information packets are released before reaching the end point node